A Therapeutic Journey of Pyridine-based Heterocyclic Compounds as Potent Anticancer Agents: A Review (From 2017 to 2021) - Alrooqi, Munira; Khan, Sikandar; Alhumaydhi, Fahad A.; Asiri, Saeed A.; Alshamrani, Meshal; Mashraqi, Mutaib M.; Alzamami, Ahmad; Alshahrani, Asma M.; Aldahish, Afaf A. (Anti-Cancer Agents in Medicinal Chemistry, 2022)
Pyridine derivatives are the most common and significant heterocyclic compounds, which show their fundamental characteristics to various pharmaceutical agents and natural products. Pyridine derivatives possess several pharmacological properties and a broad degree of structural diversity that is most valuable for exploring novel therapeutic agents. These compounds have an extensive range of biological activities such as antifungal, antibacterial, anticancer, anti-obesity, anti-inflammatory, antitubercular, antihypertensive, antineuropathic, antihistaminic, antiviral activities, and antiparasitic. The potent therapeutic properties of pyridine derivatives allow medicinal chemists to synthesize novel and effective chemotherapeutic agents. Consequently, the imperative objective of this comprehensive review is to summarize and investigate the literature regarding recent advancements in pyridine-based heterocycles to treat several kinds of cancer. Furthermore, the performances of pyridine derivatives were compared with some standard drugs, including etoposide, sorafenib, cisplatin, and triclosan, against different cancer cell lines. We hope this study will support the new thoughts to pursue the most active and less toxic rational designs.
Keywords: Pyridine